Corn palaces and butter queens : a history of crop art and dairy sculpture - Simpson, Pamela H. (University of Minnesota Press, 2012)
Between 1870 and 1930, from county and state fairs to the world's fairs, large exhibition buildings were covered with grains, fruits, and vegetables to declare the rich agricultural abundance of the US. At the same fairs ice-cooled cases enticed fairgoers to marvel at butter sculpture models including cows, buildings, flowers, and politicians, all proclaiming the rich bounty and unending promise held by the region. Often viewed as mere humorous novelties - fun and folksy, but not worthy of serious consideration - these lively forms of American art are described in this book.